Medizinische Aspekte der Auswahl eines neuen olympischen Hochleistungssegelbootes - Schonle, C. (Sportverletzung Sportschaden, 1998)
For the 2000 Olympic Sailing-Regatta the Medical Commission of the International Sailing Federation (ISAF) analysed different high performance dinghy boats from the medical point of view. The hull of the boats and the modern styled sails increase the forward force. Special outriggers compensate the shearing forces, by which different weights of the sailors make no longer a difference in case of moderate winds. The high distance between boat and boom is favorable to prevent head injuries. But in some boats many clips, rollers, ropes, hooks are installed in those areas, where the helmsman and the foredeck hand are active. The area between the outrigger tube should be covered with fabric being pervious to water: in case of a sailor's slip off or an overturn of the boat no part of the body can be squeezed. The foot straps mostly enclose the metatarsus: At manoeuvres or capzising a foot-fracture could happen. The selected boat for the Olympic Games was the 49er.